The growth and yield performance of oyster mushroom (Pleaurotus ostreatus Fries) using fish wastewater as fertilizer. - Arroyo, Karen Tingson
Fruiting bags were inoculated with oyster mushroom spawn, and after a month incubation, the growing mushrooms were assessed using the parameters of number, weight, length, and diameter., Results showed the weight of oyster mushrooms was heaviest when substrate was sprayed with plain water. However, the number of mushrooms harvested, their length, and the width of the pilei were not affected by spraying the substrate with urea or moistening these with up to 30 can result in good production; 3)neither nitrogen nor urea may be a critical factor for growth of oyster mushroom on sawdust; and 4) high amount of phosphorus and low potassium content of fish wastewater are favorable for oyster mushroom growth. B:20 C:30 Oyster mushroom, Pleurotus ostreatus, is an edible wood-inhabiting fungi that continues to gain popularity in the Philippines, as well as in other tropical countries. With the use of modern technology, this mushroom can be grown in the Philippines provided sufficient moisture is present. Its present cultivation is limited perhaps due to insufficiency of planting materials and the limited knowledge about its culture. The main objective of the study was to establish the possibility of the replacement urea, the commonly used fertilizer for mushroom cultivation, by fish wastewater. The study also aimed to compare the effects of different concentrations of fish wastewater on the growth of mushrooms and determine which treatment produced the best results. A total of five groups were used: two control groups (positive and negative - using urea and water respectively) and three experimental groups, the latter with different concentrations of fish wastewater serving as alternative fertilizer (A:10 fish wastewater. The conclusions reached were: 1) when using sawdust as substrate for oyster mushroom cultivation, it is best to simply use water to maintain the moisture of the material; 2) sawdust used in combination with low concentration of fish wastewater (10